2019
DOI: 10.5604/01.3001.0013.3401
|View full text |Cite
|
Sign up to set email alerts
|

Clinical experience of narrow band imaging (NBI) usage in diagnosis of laryngeal lesions

Abstract: Introduction: One of the most recent methods used in imaging of the larynx is narrow band imaging (NBI). NBI enables us to detect specific patterns of pathological angiogenesis suggestive of premalignant or neoplastic lesions. The aim of the study was to compare imaging of laryngeal lesions in white light endoscopy (WLE) and NBI in relation to histopathological examination. Material and methods: 333 patients with laryngeal lesions underwent endoscopic evaluation in WLE and NBI. Sensitivity, specificity, positi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 6 publications
1
21
0
Order By: Relevance
“…The results obtained in group A are in accordance with those reported in literature with a similar cohort of patients [1,9,10]. In particular, Vilaseca et al [1] showed that accuracy improved from 74.1% with WLE to 88.9% with NBI and demonstrated additionally, a better PPV (NBI: 89% vs. WLE: 74%).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The results obtained in group A are in accordance with those reported in literature with a similar cohort of patients [1,9,10]. In particular, Vilaseca et al [1] showed that accuracy improved from 74.1% with WLE to 88.9% with NBI and demonstrated additionally, a better PPV (NBI: 89% vs. WLE: 74%).…”
Section: Discussionsupporting
confidence: 90%
“…In particular, Vilaseca et al [1] showed that accuracy improved from 74.1% with WLE to 88.9% with NBI and demonstrated additionally, a better PPV (NBI: 89% vs. WLE: 74%). In addition, Popek et al [9] showed a PPV of 97.7% for NBI vs. 79.6% for WLE.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Vascular structure alterations due to microvessel proliferation, one of the first signs of malignant transformation, can be visualized with NBI on the mucosal surface [34]. Epithelial changes such as plaque morphology (smooth, elevated, rough) and microvascular NBI characteristics play a significant role in the differential diagnosis of benign and malignant lesions [35][36][37][38][39][40]. First, a 5-degree scale of the vascularization of pathological changes (Ni 2011) was established by Ni.…”
Section: Nbi Classificationsmentioning
confidence: 99%
“…Klimza et al 5 Piazza et al 14 Ni et al 16 Ni et al 15 Popek et al 4 Number to this gap in the number of articles which used one classification rather than the other one, we cannot include this topic as an evaluation criterion in the present review.…”
Section: Authorsmentioning
confidence: 99%